Behaviour of functionalized multi-walled carbon nanotubes (MWCNTs) as conductive nano-ink in isopropyl alcohol solvent - Abdul Aziz, Nur Haziqah; Jaafar, Haslina; Mohd Sidek, Roslina; Shafie, Suhaidi; Hamidon, Mohd Nizar; Wagiran, Rahman (American Scientific, 2021)
This paper presents the preparation of dispersion solutions for conductive nano-ink for inkjet printers which included filler, vehicle (solvent) and additive. For fillers, multi-walled carbon nanotubes (MWCNTs) encounter major problem such as poor dispersion resulting in agglomeration, sedimentation and unstable solution, causing nozzle clogging. MWCNTs consist of two main functional groups, namely carboxyl (−COOH) and hydroxyl (−OH) groups dispersed in isopropyl alcohol (IPA) solvent. Each functional group showed good performance as a filler after dispersing in IPA. However, MWCNT-OH has better conductivity with lower resistance of 11.3 kΩ compared to MWCNT-COOH of 15.1 kΩ. It is important for MWCNTs to have good behaviour as a filler to produce stable and high conductivity nano-ink with resistance range in kilo-ohms (kΩ). In addition, dispersing solvent is also important to ensure dispersion stability as well as maintain the performance of the filler.